DEVELOPMENT OF MULTIMEDIA-BASED INSTRUCTIONAL OF NATURAL SCIENCE IN SOLAR SYSTEM MATERIAL IN THE GRADE IX FOR HEARING IMPAIRMENT STUDENTS - Andriani, Nurvita Dwi; Praherdhiono, Henry (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
Hearing impairment students have limitation in obtaining information. Hearing impairment students needs a multimedia-based instructional to visualize a subject matter as a learning experience. This study was aimed at producing a theoretically and empirically valid multimedia-based instructional of Natural Science in Solar System material which is reviewed by experts and could be implemented in Segment B of SMPLB (Hearing impairment students). This study employed a research and development (R&D) model by William W. Lee and Diana L. Owens. Overall, the multimedia-based instructional of Natural Science in Solar System material for Segment B of SMPLB (Hearing impairment students) was valid